Mortality of the personnel of an interforce military shooting range in Sardinia, Italy: 1990-2010 - Satta, Giannina; Ursi, Michela; Garofalo, Elisabetta; Masala, Elisabetta; Pili, Claudia; D'Andrea, Ileana; Tocco, Annarita; Avataneo, Giuseppe; Flore, Maria Valeria; Campagna, Marcello; Cocco, Pierluigi (La Medicina del Lavoro, 2017)
Background: As several media reports suggested an increase in cancer mortality in the surrounding area, we investigated the mortality experience of the military personnel of the Interforce shooting range of Salto di Quirra (PISQ) in Sardinia, Italy. Methods:  Based on the PISQ registers, we reconstructed the cohort of 6,828 military personnel who had been employed at PISQ for at least six months on January 1, 1990 or entered subsequently up to June 30, 2005. We searched for life status or date, place, and cause of death of each cohort member up to December 31, 2010. Based on job and operating department, we preliminarily assessed exposure of each cohort member to radiofrequencies, solvents, nanoparticles, servicing in shooting ranges, participation to peacekeeping operations abroad, and undergoing vaccination procedures while in service. For each cause of interest, we calculated the standardized mortality ratio (SMR) and its 95% confidence interval, based on the Italian and regional rates specific for age, gender and year of follow-up. Results: Mortality from all causes showed a significant decrease over the expectation, based on the national and regional mortality rates (based on national rates: SMR=78, 95% CI 60-101; based on regional rates: SMR=66, 95% CI 52-84). Deaths from haemolymphatic malignancies matched the expectation from regional rates (7 cases vs 6,3 expected; SMR=111, 95% CI 38-326). We observed two deaths from neoplasms of the haemolymphopoietic system against 0.5 expected among solvent exposed cohort members. We did not observe any significant increase in mortality from all causes or specific causes of death in relation to the exposures we investigated. Conclusions: The study size was too small, and the follow-up not prolonged enough to conclude whether the operational activities at PISQ did result or not in increased risks of specific causes of death, including cancers, among the military personnel. Further follow-up will be needed before final conclusions can be drawn.